2022
DOI: 10.1155/2022/3471912
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping and Rhizobium Inoculation Affected Microclimate and Performance of Common Bean (Phaseolus vulgaris L.) Varieties

Abstract: A field experiment was carried out at Hawassa, during the 2020 cropping season with the objective to evaluate the impact of maize-common bean intercropping and Rhizobium inoculation on microclimate, growth, and yield of common bean varieties. Treatments consisting of two common bean varieties, two levels of inoculation and three spatial arrangements of common bean with another sole maize were laid out in a factorial arrangement in a randomized complete block design (RCBD) with three replications. The results r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…These results are similar to what was reported by Victoria et al (2022); where it was noted that intercropping reduced disease progression in the field. Low AUDPC in potato intercrops may also be because of changes to microenvironments in which intercrops have been presumed to affect the humidity, temperature, and airflow of field microenvironments; thereby reducing the impact on the onset and development of diseases (Shemeles et al, 2022). This is an area that deserves more elaborate investigations with regards to the potato bacterial wilt, under Kenyan conditions.…”
Section: Area Under Disease Progress Curve (Audpc)mentioning
confidence: 99%
“…These results are similar to what was reported by Victoria et al (2022); where it was noted that intercropping reduced disease progression in the field. Low AUDPC in potato intercrops may also be because of changes to microenvironments in which intercrops have been presumed to affect the humidity, temperature, and airflow of field microenvironments; thereby reducing the impact on the onset and development of diseases (Shemeles et al, 2022). This is an area that deserves more elaborate investigations with regards to the potato bacterial wilt, under Kenyan conditions.…”
Section: Area Under Disease Progress Curve (Audpc)mentioning
confidence: 99%
“…Ref. [31] showed that some bean cultivars that are better adapted to rhizobial inoculation, in the same way that there are also soils that are not adapted to this practice. Considering this information, it is possible to observe that there is a difference between commercial bean cultivars; that is, cultivars considered more efficient for FBN may respond to native or exogenous rhizobia, while others may Analyzing the results found for W100 in the comparison between cultivars, it is possible to verify that there was a difference in their adaptation, either due to the type of treatment applied or the influence of seasonality and soil type; the genetic differences between the bean plants also influence results.…”
Section: Components and Grain Yieldmentioning
confidence: 99%
“…Ref. [31] showed that some bean cultivars that are better adapted to rhizobial inoculation, in the same way that there are also soils that are not adapted to this practice. Considering this information, it is possible to observe that there is a difference between commercial bean cultivars; that is, cultivars considered more efficient for FBN may respond to native or exogenous rhizobia, while others may adapt only to nitrogen fertilization.…”
Section: Components and Grain Yieldmentioning
confidence: 99%